Phytochemical Screening and TLC Profiling of Combination Extracts of Avocado (Persea americana Mill.) and Papaya (Carica papaya) Leaves from Timor Island - Kafelau, Marianus; Kopon, Aloisius Masan; Baunsele, Anselmus Boy; Tukan, Maria Benediktas; Leba, Maria Uron; Komisia, Faderina; Boelan, Erly Grizca (Indonesian Journal of Chemical Research, 2022)
Traditionally in the village of Alor, East Nusa Tenggara Province, a combination of avocado and papaya leaves is often used to treat malaria. To be able to be developed as an ingredient in traditional medicine, it is necessary to conduct preliminary research to determine the content of secondary metabolites contained in the combination of avocado and papaya leaves. This study aims to determine the secondary metabolites contained in avocado and papaya leaves through phytochemical screening and Thin Layer Chromatography (TLC) analysis. Extraction was carried out using methanol solvent by maceration, and the extract yield was 91.4%. Testing the content of secondary metabolites in avocado and papaya leaf extracts was carried out by phytochemical screening. Furthermore, the TLC test was carried out to confirm the presence of a positive group of compounds on phytochemical screening, and to determine the chromatographic profile of the extract. After being tested by phytochemical and TLC analysis, the extract contains several metabolites, including flavonoids, alkaloids, tannins, saponins, and steroids. The TLC system used in this study can separate the phytochemical content and give positive results that confirm the results of the phytochemical screening.